IMPROVING BUSINESS PERFORMANCE THROUGH COMPETITIVE ADVANTAGE: A STUDY ON SMES IN BANJARMASIN, INDONESIA - Agustina T. (Eurasia: Economics & Business, 2019)
This study aims to describe and analyze the learning, locus of control, motivation, competitive advantage and performance of Micro, Small and Medium Enterprises (SMEs) in Banjarmasin, Indonesia. A purposive random sampling was used as the data collection technique. The Structural Equation Modeling (SEM) analysis technique by AMOS program was used to process the data from 100 respondents. Study results showed that learning, locus of control and motivation affects the competitive advantage. Likewise, learning, locus of control and motivation influence the business performance. The competitive advantage affects the SMEs performance in Banjarmasin. Motivation gives a dominant direct effect on the competitive advantage. Locus of control gives the dominant direct effect on the business performance. Locus of control and motivation give greater total effects than the direct effect so that the competitive advantage is proven as an intervening variable that mediates learning, locus of control and motivation to the business performance. It means that learning, locus of control and motivation significantly affects the business performance through the SMEs competitive advantage in Banjarmasin. The higher the business performance formed by the contribution of learning, locus of control and motivation, the higher the SMEs competitive advantage.